(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
The paper analyzes the EU Strategy to tackle Organized Crime that was presented by the European Commission on 14 April 2021 with the aim to outline the main areas of intervention in the fight against organized crime groups, to strengthen information exchange and cooperation between member States and evaluate the effectiveness of Framework Decision 2008/841/JHA of 24 October 2008 on the fight against organized crime.